High-resolution X-ray computerized tomography to characterize localized corrosion rates of carbon steel in contaminated steam cycles - Akash Ganesan; Renaldo Springer; Andrew Howell; Brad Burns; Derek M. Hall (npj Materials Degradation)
Abstract Aging power plants must cycle more frequently as the sector shifts to renewables, increasing susceptibility to contamination, localized corrosion, and tubing failures. Herein, we examine how high-resolution X-ray computed tomography can provide new insights into the relationship between localized, general corrosion rates and boiler water chemistries. The following study examines how chloride and sulfate contaminants impact carbon steel corrosion at 300 °C and 12.4 MPa, which are typical conditions in utility boilers and evaporators. The localized corrosion rates caused by sulfate and chloride contamination were, on average, 2.69 and 5.55 mm y−1, respectively, an order of magnitude larger than the uniform corrosion rates, 0.16 and 0.40 mm y−1 at the same conditions. Chloride caused a few deep pits, whereas sulfate tended to form more shallow pits during the same timeframe. This study highlights the need to detect and quantify localized corrosion in boiler tubing and the effectiveness of X-ray computed tomography in assessing corrosion rates.